Ultravysokomolekulární polyethylen pro kloubní náhrady se zvýšenou životností - Šlouf, Miroslav; Vacková, Taťana; Nevoralová, Martina; Mikešová, Jana; Dybal, Jiří; Pilař, Jan; Zhigunov, Alexander; Kotek, Jiří; Kredatusová, Jana; Fulín, Petr (Chemické listy, 2013)
Ultrahigh molecular weight polyethylene (UHMWPE) is a key component of modern total joint replacements (TJR). The most frequently replaced human joints are hips and knees, followed by shoulders, elbows, etc. However, UHMWPE liners are the most loaded components of the implants. Consequently, the main materialrelated reasons of TJR failures are wear and oxidative degradation of the polymer. Resistance to wear (i.e. release of microscopic particles from the polymer surface) is increased by radiation-induced crosslinking. Oxidation stability (i.e. resistance of polymer to chain scissions and deterioration of mechanical properties) is enhanced by means of suitable thermal treatment and sterilization protocols. The most recent trend is to employ a biocompatible stabilizer – vitamin E – for further improvement and finetuning of UHMWPE performance. This review summarizes the recent developments in UHMWPE modifications, which come both from the author’s institute and from the world, and which should further increase lifespan of total joint replacements.
Keywords: záření gama; Gamma Rays; biokompatibilní materiály; Arthroplasty, Replacement; artroplastiky kloubů; Polymers; lidé; alfa-tokoferol; Polyethylenes; biomechanika; Biocompatible Materials; Materials Testing; testování materiálů; polymery; Joint Prosthesis; protézy kloubů; Radiation Dosage; dávka záření; polyethyleny; alpha-Tocopherol; Biomechanical Phenomena; Humans